The identification of archaeological evidence for hawking in medieval England - Annia Kristina Cherryson (2001)
Abstract. This paper examines the archaeozoological evidence for hawking in Medieval England between AD 600 and 1600. It will initially survey the incidence of skeletal re-mains of those species closely associated with hawking during the medieval period, namely the short winged hawks, the Goshawk and Sparrowhawk, and the long winged hawks, such as the Peregrine Falcon, Kestrel and Gyrfalcon. By using criteria such as the nature of the deposition of the skeletal remains, environmental factors and by assessing the incidence of other wild species within the faunal assemblage, this paper demonstrates that in most cases a determination of wild or captive status is possible. These findings pro-vide evidence for the widespread use of hawking birds, especially the Sparrowhawk and the Goshawk in medieval England across the whole period under consideration. Further-more, the distribution of archaeozoological evidence is also indicative of the status of fal-conry as a pursuit of those with means, with manors and castles representing a third of all sites and in general these deposits contain the remains of a greater number of birds. What is perhaps more surprising is the high numbers of trained birds recovered from urban con-texts, although it should be noted that a number of the urban deposits, such as the Bedern, York and those in Southampton, are associated with high status sites.